OBSERVATION OF FEMALE DORM PRIVACY IN ISLAMIC BOARDING SCHOOLS IN WEST JAVA, INDONESIA - Rangga Firmansyah; Nazlina Shaari; Sumarni Ismail; Nangkula Utaberta; Ismar Minang Satotoy Usman (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2021)
In learning activity processes in Islamic boarding schools, students must study and live in a dormitory. It functions to replace a residential home where the privacy aspect should be taken into consideration. This study aims to observe the privacy aspects closely related to the female students' bedrooms, covering six elements examined in five case studies, including the sex-segregated dormitories, the main function of staying, visual privacy on the dimensions height of the windows, acoustic privacy, and olfactory privacy in terms of the connection between dormitory rooms. It was found that the privacy aspect in the dormitory room still lacked attention due to the addition of space functions and bathroom facilities in it. Meanwhile, adding personal facilities, such as storage and study areas, could enhance the students' privacy. Especially for the type of student bedroom, it is necessary to provide a place for drying clothes by utilizing the balcony area. Besides that, it is required to pay attention to the type, dimensions direction of window openings so that the level of privacy of female students will be more optimal.